ATG5 promotes eosinopoiesis but inhibits eosinophil effector functions - Germic, Nina; Hosseini, Aref; Stojkov, Darko; Oberson, Kevin; Claus, Meike; Benarafa, Charaf; Calzavarini, Sara; Angelillo-Scherrer, Anne; Arnold, Isabelle C.; Müller, Anne; Riether, Carsten; Yousefi, Shida; et al. (Blood, 2021)
Eosinophils are white blood cells that contribute to the regulation of immunity and are involved in the pathogenesis of numerous inflammatory diseases. In contrast to other cells of the immune system, no information is available regarding the role of autophagy in eosinophil differentiation and functions. To study the autophagic pathway in eosinophils, we generated conditional knockout mice in which Atg5 is deleted within the eosinophil lineage only (designated Atg5eoΔ mice). Eosinophilia was provoked by crossbreeding Atg5eoΔ mice with Il5 (IL-5) overexpressing transgenic mice (designated Atg5eoΔIl5tg mice). Deletion of Atg5 in eosinophils resulted in a dramatic reduction in the number of mature eosinophils in blood and an increase of immature eosinophils in the bone marrow. Atg5-knockout eosinophil precursors exhibited reduced proliferation under both in vitro and in vivo conditions but no increased cell death. Moreover, reduced differentiation of eosinophils in the absence of Atg5 was also observed in mouse and human models of chronic eosinophilic leukemia. Atg5-knockout blood eosinophils exhibited augmented levels of degranulation and bacterial killing in vitro. Moreover, in an experimental in vivo model, we observed that Atg5eoΔ mice achieve better clearance of the local and systemic bacterial infection with Citrobacter rodentium. Evidence for increased degranulation of ATG5low-expressing human eosinophils was also obtained in both tissues and blood. Taken together, mouse and human eosinophil hematopoiesis and effector functions are regulated by ATG5, which controls the amplitude of overall antibacterial eosinophil immune responses. •Eosinophil differentiation is delayed and reduced in the absence of ATG5 under both physiological and leukemic conditions.•Effector functions of ATG5-deficient mouse and human eosinophils are enhanced under in vivo conditions. [Display omitted]